Pathogenesis of psoriasis in the “omic” era. Part II. Genetic, genomic and epigenetic changes in psoriasis - Nedoszytko, Bogusław; Szczerkowska-Dobosz, Aneta; Stawczyk-Macieja, Marta; Owczarczyk-Saczonek, Agnieszka; Reich, Adam; Bartosińska, Joanna; Batycka-Baran, Aleksandra; Czajkowski, Rafał; Dobrucki, Iwona; Dobrucki, Lawrence; Górecka-Sokołowska, Magdalena; Janaszak-Jasiecka, Anna; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Psoriasis is a multifactorial disease in which genetic, environmental and epigenetic factors regulating gene expression play a key role. In the “genomic era”, genome-wide association studies together with target genotyping platforms performed in different ethnic populations have found more than 50 genetic susceptible markers associated with the risk of psoriasis which have been identified so far. Up till now, the strongest association with the risk of the disease has been proved for HLA-C*06 gene. The majority of other psoriasis risk SNPs are situated near the genes encoding molecules involved in adaptive and innate immunity, and skin barrier function. Many contemporary studies indicate that the epigenetic changes: histone modification, promoter methylations, long non-coding and micro-RNA hyperexpression are considered as factors contributing to psoriasis pathogenesis as they regulate abnormal keratinocyte differentiation and proliferation, aberrant keratinocytes – inflammatory cells communication, neoangiogenesis and chronic inflammation. The circulating miRNAs detected in the blood may become specific markers in the diagnosis, prognosis and response to the treatment of the disease. The inhibition of expression in selected miRNAs may be a new promising therapy option for patients with psoriasis.